End of social inequality ? : class, status and power under state socialism - Lane, David (London, 1982)
The arrangement of the book facilitates the discussion of three interrelated problems of social stratification as they apply to state-*societies. First, there is the relevance of the Marxist notation of class, by which we mean a social and economic group at its roots differentiated by its 'relationship to the means of production' with a common political interest against other classes. Class in this sense is a tool in the analysis of history, a causal factor in the transformation of societies. The important question here is the nature of the political structure of a society in which classes, in the formal Marxist sense, have been abolished. This is the subject matter of chapter 1 and 5.Secondly, we are concerned with the nature of social inequality in a state-socialist society. Social inequality refers to the uneven distribution of goods and values among in the population in the sense that one group may have more income or education than another and this aspect of stratifications the concern of chapter 2. Closely connected to inequality is the ranking and privilege's of individuals or groups on a scale of superiority or inferiority and these are the topics of chapter 3. In chapter 4 examine the related question of the extent to which individual statuses are available to open recruitment or conversely are restricted to certain groups.
Keywords: "Social classes Europe, Eastern"